Análise de integridade de compósito polimérico tripla camada reforçado com fibra de vidro e aplicado em tubulações de petróleo - Gomes, Italo Martins (2020)
The oil and gas industry have equipment corrosion problems due to contaminants in fluid of the reservoirs. The composits are very promising materials to mitigate this problem, with good mechanical and thermal properties, excellent corrosion resistance, because they are composed of more than one material, taking advantage of them properties. In 2010, a triple layer composite pipe for the production of oil wells was developed as an alternative to API 5L Grade B steel normaly used and more susceptible to corrosion. In present work were colected this composites samples in three oil wells from three different areas in the state of Rio Grande do Norte, which have been operating with this material for some years. The samples were analyzed by tensile test and finite elements method, optical microscopy, scanning electron microscopy, differential scanning calorimetry, thermogravimetric analysis and water absorption test and compared with a sample of a pipe control never used. The results showed not significants changes in the thermal and increased water absorption properties of the field samples compared to the control sample. It has also been seen that this material is safe and operationally suitable for use in the field and the tensile test is not ideal to characterize the complex mechanical behavior of this composite. Also, some areas presented fiber glass with insufficient epoxy and low interaction between the intermediate and outer layer, indicating problems in manufacturing of pipes that need to be corrected. Were identificated cracks in the samples of oil wells that must have been nucleated due service of the pipe in field and due the presence of interface with deficient interaction between the intermediate and outer layers